Faktor Kesukarelaan Dalam Pengunduran Diri Pekerja/Buruh: Studi Putusan Pengadilan Hubungan Industrial Di Medan No. 262/Pdt.Sus-Phi/2017/Pn.Mdn, Di Banda Aceh No. 5/Pdt.Sus- Phi/2016/Pn.Bna, Dan Di Palu No. 18/Pdt.Sus-Phi/2015/Pn.Pal - Andriani, Patricia Cindy; Kiswandari, Melania (UI Scholars Hub, 2019)
Resignation is one of the mechanisms for terminating employment relations that requires voluntary factor in the employee’s action. However, in a number of cases, the resignation was actually not based on the initiative of employee, but was motivated by the employer’s action who put employee into difficult situation so that he/she had no choice but to resign. Therefore, it is necessary to further examine the regulations regarding termination of employment and their implementation at the Industrial Relations Court level toward cases about the employee’s involuntary resignation in decision no. 262/Pdt.Sus- PHI/2017/PN.Mdn, no. 5/Pdt.Sus-PHI/2016/PN.Bna, and no. 18/Pdt.Sus- PHI/2015/PN.Pal. The research is a normative juridical research by comparing 3 (three) court decisions, which has descriptive analytical.